2009
DOI: 10.3109/17453670903110675
|View full text |Cite
|
Sign up to set email alerts
|

Positive nasal culture of methicillin-resistantStaphylococcus aureus(MRSA) is a risk factor for surgical site infection in orthopedics

Abstract: Background Although nasal carriage of MRSA has been identified as one of the risk factors for surgical site infection (SSI) with MRSA, there have been no reports of this in the orthopedics field.Methods This prospective observational cohort study included 2,423 consecutive patients who were admitted to our department over 26 months and who underwent orthopedic surgery. We examined the relationship between pre-existing nasal MRSA and subsequent occurrence of SSI with MRSA.Results 63 patients (2.6%) had a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 31 publications
4
31
0
4
Order By: Relevance
“…In our study, we found that admission 24 hours or more before surgery increases the incidence of infection and should be avoided in those cases that are not emergent or semiurgent (OR, 7.09; 95% CI, 3.93-12.7; p \ 0.001). Positive nasal screening for S aureus including methicillin-resistant S aureus was found to increase PJI in previous studies [14,24]. Our data show similar findings.…”
Section: Staphylococcus Aureus 15supporting
confidence: 82%
“…In our study, we found that admission 24 hours or more before surgery increases the incidence of infection and should be avoided in those cases that are not emergent or semiurgent (OR, 7.09; 95% CI, 3.93-12.7; p \ 0.001). Positive nasal screening for S aureus including methicillin-resistant S aureus was found to increase PJI in previous studies [14,24]. Our data show similar findings.…”
Section: Staphylococcus Aureus 15supporting
confidence: 82%
“…Infection spreads in hospitals because of close contact and the point that hospitals staff and patients carry antibiotic resistant S. aureus specially (MRSA) in their nose or on their skin [3,4,17].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococci, especially Staphylococcus epidermidis, are part of the normal flora of human skin, and gastrointestinal and respiratory tracts. S. aureus is the most significant pathogen of human infections, mainly wound, respiratory tract and skin infections that is associated with several pathological processes such as food poisoning, pneumonia, bacteremia, folliculitis, and osteomyelitis [2][3][4]. This organism is one of the most important causes of nosocomial infections, which become increasingly more resistant against the antibiotics of beta-lactam and vancomycin groups [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Yano et al 9 reported that positive nasal culture of MRSA is a risk factor for SSI in elective orthopaedics. Of 2423 patients included in the study, 63 (2.6%) were nasal MRSA carriers.…”
Section: Discussionmentioning
confidence: 99%